The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1121/1.2204437
|View full text |Cite
|
Sign up to set email alerts
|

Low-level otoacoustic emissions may predict susceptibility to noise-induced hearing loss

Abstract: In a longitudinal study with 338 volunteers, audiometric thresholds and otoacoustic emissions were measured before and after 6 months of noise exposure on an aircraft carrier. While the average amplitudes of the otoacoustic emissions decreased significantly, the average audiometric thresholds did not change. Furthermore, there were no significant correlations between changes in audiometric thresholds and changes in otoacoustic emissions. Changes in transient-evoked otoacoustic emissions and distortion-product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…Several studies have reported a significant correlation between a reduction in TEOAE amplitude and the presence of NIHL (Hall & Lutman, 1999;Jansen et al, 2009). Furthermore, Lapsley-Miller, Marshall, Heller, and Hughes (2006) found decreased group average OAE amplitudes after several months of noise exposure, whereas the average audiometric thresholds did not show any change. In the current study, it was hypothesized that if the apparent notches were a result of TTS, then possible changes in TEOAE amplitude might accompany the notch, as suggested by Helleman, Jansen, and Dreschler (2010).…”
Section: Examination Of Notched Audiograms and Teoaesmentioning
confidence: 94%
“…Several studies have reported a significant correlation between a reduction in TEOAE amplitude and the presence of NIHL (Hall & Lutman, 1999;Jansen et al, 2009). Furthermore, Lapsley-Miller, Marshall, Heller, and Hughes (2006) found decreased group average OAE amplitudes after several months of noise exposure, whereas the average audiometric thresholds did not show any change. In the current study, it was hypothesized that if the apparent notches were a result of TTS, then possible changes in TEOAE amplitude might accompany the notch, as suggested by Helleman, Jansen, and Dreschler (2010).…”
Section: Examination Of Notched Audiograms and Teoaesmentioning
confidence: 94%
“…The present study evoked the DPOAE at two intensity levels to investigate the amplitude differences at 45/55 dB SPL (moderate level) and 55/65 dB SPL (high level). Research has shown that OAE testing may be a possible predictor of future NIHL and OAEs may decrease in amplitude prior to changes in audiometric thresholds [21,22]. Due to the possibility that changes in OAEs may be early indicators of hearing loss, 43 of the 115 participants completed OAE testing in addition to the other audiologic testing.…”
Section: Methodsmentioning
confidence: 99%
“…Animal work indicates that MOC tests at low sound levels can be predictive of MOC anti-trauma strength (Maison and Liberman, 2000) but this does not rule out low-to-high-level differences. Prospective tests in humans are needed to show how well MOC tests predict susceptibility to acoustic trauma, e.g., MOC tests applied at the start of a person’s work in a loud-sound environment (e.g., Lapsley Miller et al, 2006). …”
Section: Tests To Predict Susceptibility To Acoustic Trauma and Auditmentioning
confidence: 99%